Load-Bearing Capacity of Concrete Hollow Blocks Containing Rice Husks - T. UNIANA , EUGENE; S. MOSTRALES, DANIEL; N. OREJUDOS, JERSON (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This research measures the feasibility of Rice Husks (RH) as additves in cement-aggregate mixture ofa load-bearing Concrete Hollow Block (CHB) Results show that 4% of Pulverized Rice Husks (PRH) mixed with cement, and ag gregates at 1:3 mix ratio, plus water, gives a compressive strength of 10.72 MPa(1.555 psi) and 11.39 MPa (1,652 psi) at age 14 and 28 days, respectively, of a load-bearing CHB in conformity with the ACI, British, and Philippine National Standards. Concrete Hollow Blocks (CHB) containing PRH result to a higher compressive strength compared to CHB's containing Unpulverized Rice Husks (URH);1% and 2.69% by weight URH mixed with 1:3 ratio of cement and aggregates, give 8.64 MPa (1,254 psi) and 7.30 MPa (1,059 psi), respectively. at age 28 days. A mix ratio of l:5 at 1% URH gives 7.05 MPa (1,023 psi).